Determination of 2,4,6-trichloroanisole by cyclic voltammetry - Freitas, P. (2012)
The electrochemical reduction of 2,4,6-trichloroanisole (TCA), a chlorinated arene with electron-donating substituents, was evaluated by cyclic voltammetry (CV). TCA is a major concern for the winery industry since it is related with “cork taint”, a wine defect. The results obtained showed that CV could be used to detect and quantify TCA in standard solutions. Linear relationships could be set between the current amplitude and TCA concentrations (R>0.990) with detection and quantification limits of 0.08 and 0.26 ppm. Although, these preliminary limits are higher than the human sensory threshold (5 ppt in wine), the simplicity of the methodology confers this study a possible role in the development of more efficient and less expensive process for TCA detection in the industry.